Discriminative power of features used by forensic document examiners in the analysis of handwriting - Pervouchine, Vladimir (2008)
Forensic document examintation of handwriting to determine the authorship of questioned documents has been in use for more than 100 years. However, in recent court cases the acceptability of forensic document analysis has been successfully challenged. It has been pointed that the techniques, although intuitively reasonable, lack strong scientific foundation. In this thesis a study of discriminative power of a number of character-level features is presented. The features correspond to those used by forensic document examiners. It was shown that most of the studied features indeed possess discriminative power and hence their use in forensic analysis of handwriting is justified.